أثر تطبيق إدارة الجودة الشّاملة على جودة التّعليم دراسة ميدانيّة على جامعة سبها اللّيبيّة - حسن محمد ميهوب بالحمرة
This study aims at identifying the effects of implementing the Total Quality Management (TQM) on the quality of education in the Sebha University in Libya. The researcher adopted the descriptive and analytical approach because of its suitability to the nature of the current study. Since the study population consists the whole employees in the Sebha University6 Libya6 the actual study comprises the male and female employees of the University. And the selection of the employees for the study was done randomly from the study population. In order to achieve the objective of the study6 questionnaire was used as a tool for data collection. The analysis of the questionnaire was done with the use of the SPSS programme. The study indeed arrived at some findings. The main findings of the study include the following: the existence of high standard in the quality of education and educational performance6 and the area of regulatory obstacles; the existence of medium standard in the area of quality of culture6 available resources and monitoring. The findings of the study also include the existence positive relationship between continuity and the quality of education in the sebha University. There is also positive relationship between the educational performance the quality of education6 as well as the existence of relationship between the quality of culture and the quality of education in the University. Likewise6 there. exists a negative relationship between the regulatory obstacles and the quality of education6 so also a positive relationship between available resources and the quality of education in the sebha University.